ChemInform Abstract: A Simple and Convenient Method for Synthesis of New Aminonaphthoquinones Derived from Lawsone by Catalytic Multicomponent Mannich Reaction. Issue 52 (29th December 2014) - Fiorot, Rodolfo G.; Allochio, Joao F. Filho; Pereira, Thieres M. C.; Lacerda, Valdemar Jr.; dos Santos, Reginaldo B.; Romao, Wanderson; Greco, Sandro J.
Abstract Improved reaction conditions are developed for the three component Mannich reaction of lawsone (I) with aldehydes and amines to give new aminonaphthoquinones.